2018
DOI: 10.1155/2018/3924517
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Pulmonary Hypertension and Its Clinical Correlates: A Cross-Sectional Study

Abstract: Background Health-related quality of life (HRQoL) impairment is common in pulmonary hypertension (PH), but its clinical predictors are not well established. This study aims to characterize the HRQoL of patients with pulmonary arterial hypertension (PAH) and other precapillary forms of PH (pcPH) and to explore its clinical correlates. Materials and Methods A cross-sectional, observational study of patients with documented PAH and other forms of pcPH. Patients completed two patient-reported outcome measures (PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 33 publications
5
24
4
Order By: Relevance
“…After completion of CAMPHOR, the results obtained in the three domains show that our attended PAH population (WHO FC I-III) experiences different levels of impairment due to disease. Our results were slightly lower than those reported by Reis et al 5 in a similar cohort of patients (69.4% in WHO FC I/II vs 63.9% in our study) and reasonably lower than those reported by McCabe et al for patients with idiopathic PAH and CTEPH) 18 . Regarding factors that could affect these results and consistent with those reported by Small et al 19 , in the three CAMPHOR domains the scores were better in those patients receiving only one drug since 65.2% of WHO FC I/II and 46.2% of WHO FC III patients in our study were undergoing monotherapy for PAH.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…After completion of CAMPHOR, the results obtained in the three domains show that our attended PAH population (WHO FC I-III) experiences different levels of impairment due to disease. Our results were slightly lower than those reported by Reis et al 5 in a similar cohort of patients (69.4% in WHO FC I/II vs 63.9% in our study) and reasonably lower than those reported by McCabe et al for patients with idiopathic PAH and CTEPH) 18 . Regarding factors that could affect these results and consistent with those reported by Small et al 19 , in the three CAMPHOR domains the scores were better in those patients receiving only one drug since 65.2% of WHO FC I/II and 46.2% of WHO FC III patients in our study were undergoing monotherapy for PAH.…”
Section: Discussioncontrasting
confidence: 79%
“…These proportions were higher than those reported in the REVEAL registry 20 and previous studies with measures of HRQoL that show proportions of WHO FC III-IV near 70% 18,19,21 . The association between WHO FC and CAMPHOR scores has been well described in previous cohorts 5 . We found statistically significant differences for the WHO FC and the 'Symptoms' (p = 0.004), 'Activities' (p = 0.005) and 'Quality of life' (P = 0.02) domains of CAMPHOR, showing that PRO's are good predictors of the functional capacity.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The quality of life in patients with untreated chronic PH is poor, usually similar to the quality of life in patients with advanced stages of pulmonary, cardiac or renal disorders [25]. In our study, patient quality of life significantly improved after completed BPA in comparison to baseline status (p < 0.001 for both EQ5D-5L score and overall health status).…”
Section: Effect Of Bpa On Quality Of Lifesupporting
confidence: 52%
“…Quality of life in patients with untreated chronic pulmonary hypertension is poor, and is usually similar to quality of life in patients with advanced stages of pulmonary, cardiac or renal disorders 12 . Using the EQ5D-5L questionnaire for quality of life evaluation, we observed significant improvements both in EQ5D-5L score and overall self-assessed health status in comparison to values at therapy initiation after 5 months of riociguat treatment.…”
Section: Discussionmentioning
confidence: 99%